Postural deviations in the school environment - a field study centered on the dimension of Postural awareness - ben ali, ridha; Mansouri, nabil (sports creativity, 2024)
This study addressed postural deviations in the school environment by shedding light on the dimension of postural awareness among students of the Institute of Science and Technology of Physical and Sports Activities in Bouira, relying on the descriptive approach through a questionnaire form applied to 23 students in an intentional manner. It was concluded that The degree of postural awareness to prevent postural deviations among students of the Institute of Science and Technology of Physical and Sports Activities is high, similar to cognitive and motor postural awareness.